Exploring the therapeutic potential of reading: Case studies in diary-assisted reading - Green, Kelda (Frontiers in Psychology, 2022)
This article explores the impact that literary texts can have on real lives and considers how, as researchers, we can get closer to the authentic, first-hand experience of reading to better understand its potential therapeutic mechanisms. Three case studies, based on reading diaries kept over a period of 2 weeks and subsequent semi-structured interviews, are presented here, to demonstrate what it is that literature can do to and for us. The methodology used to collect the case studies offers a simple and replicable template both for encouraging deep reading and for capturing its resulting therapeutic and psychological outcomes. By highlighting the real experiences of readers as they encounter and engage with a complex and unfamiliar literary text, this article aims to demonstrate how empirical research methodologies can add new purpose and meaning to literary study, and equally, show how “literary thinking” can contribute to the methodologies of psychological study and the formulation of psychological therapies.